Optimization Time for Antibacterial Production of Endophytic Fungi Isolated from Bidara Root (Ziziphus mauritiana Lam.) - Annisa, Khusnul; Fitriana, Fitriana; Amirah, Sitti (Journal Microbiology Science, 2024)
Research on optimization time for antibacterial production of endophytic fungal isolated from bidara root (Ziziphus mauritiana Lam.) has been conducted, with the aim of determining the optimum production time for antibacterial compounds. Endophytic fungi are a group of fungi that live within plant tissues without causing harm to their host plants. In this research, the roots of bidara were isolated and purified using PDA media, isolates were followed by screening endophytic fungi isolates against test bacteria. The results of the endophytic fungal isolation from the bidara roots yielded 10 endophytic fungal isolates. The screening test against the test bacteria showed the largest inhibitory zone for IFAZ-6. Subsequently, the growth curve of these isolates was determined through fermentation using MYB media using a shaker speed of 200 rpm at a temperature of 25-28°C for 27 days. Then, mycelia and supernatant were collected on days 11, 13, 15, 17, 19, 21, 23, 25, and 27 with a 48-hour interval. The mycelia were weighed until a constant weight was obtained, while the supernatant was used to test the activity against the test bacteria using MHA media. The growth curve results indicated a stationary phase on day 21. The antibacterial activity test showed that Isolate IFAZ-6 reached optimum activity on day 27 with an inhibitory zone of 12.33 mm against Salmonella thypi.